PROMOTING MORE ENJOYABLE EFL READING LEARNING ENTERPRISES THROUGH AN ONLINE EXTENSIVE READING STRATEGY - wijaya, kristian florensio (Universitas Teknokrat Indonesia, 2024)
AbstractThe crux of modern EFL reading learning enterprises is no longer dependable on satisfying reading scores achieved by second language learners, yet it has been shifted to more transformative reading learning purposes. All these coveted EFL reading learning aspirations are exactly represented in an online extensive reading strategy where second language learners are rigorously commissioned to explore a huge number of digital reading passages to be accompanied by increasingly-rate reading velocity, fluency, and comprehension skills. In harmony with all these rewarding online extensive reading values, the researcher conducted this present small-scale library investigation to specifically unearth the extent an online extensive reading strategy can induce more favorable reading learning enterprises for worldwide EFL learners. Toward that end, the researcher harnessed an open-coding and a thematic analysis approach to produce more reliable, relatable, comprehensible, and applicable research results to be further internalized by the targeted EFL parties. To increase the relevancy of each single analyzed research result, the researcher selected 20 previously published online extensive reading strategy studies resided in varied reputable journal article platforms. The thematically categorized research results highly suggested worldwide second language reading educationalists start applying an online extensive reading strategy at the outset of their quotidian reading learning dynamics by which EFL learners can progressively transfigure into more motivated L2 readers under the limelight of more emotionally-supportive reading learning climates. These already-taken research results provide more exhaustive insights for globalized EFL reading experts, practitioners, and educationalists concerning the indispensability of online extensive reading strategy maximization in correspond with changeable reading learning environments. Keywords: Online extensive reading strategy, globalized EFL learners, library investigation, thematic analysis